Pengembangan Perikanan Tangkap Pelagis Kecil untuk Pemberdayaan Nelayan di Kota Palopo - Suardi Suardi; Ummi Maksum Marwan; Andi Mi'rajusysyakur Muchlis (Universitas Andi Djemma, 2022)
The utilization of small pelagic fish in the coastal water of Palopo City has not exceeded the critical level Maximum Sustainable Yield (MSY), but has expertised over fishing, e.g. total annual fishing effort exceeded the optimum effort. Now days, fishing units operated local by fisherman mostly composed were traditional categories. Based on biological, technical, and socio-economical aspects, purse seine can be selected as an appropriate gear for local fisheries development. Adoption of the selected technology faces some constraints on human capacity; the selected purse seine only few fishermen experienced operating purse seine. Local fisheries development can by carried out by adopting the technology without causing excessive optimum fishing effort. This can be achieved by replacing in-efficient payang fishing unit by purse seine. This technological development must be accompanied with development of human resources (i.e. fishermen) by giving the a training program of haw to operate and manage purse seiners.